Emulsifying properties of milk protein concentrate functionalized by supercritical fluid extrusion. Issue 10 (22nd July 2020) - Gopirajah, Rajamanickam; Singha, Poonam; Javad, Sumera; Rizvi, Syed S. H.
Abstract: Emulsifying properties of milk protein concentrate functionalized by supercritical CO2 extrusion process were studied. Three levels of oil (20, 40, and 60% w/w) and protein dispersions in water (1, 2, and 4% w/w) were employed to study the emulsifying properties of functionalized milk protein concentrate (f‐MPC85) and compared with emulsions stabilized by unextruded commercial milk protein concentrate (c‐MPC85) and commercial sodium caseinate (NaCas). High viscosity (35 Pa·s), shear‐thinning emulsions were obtained having uniform droplet size distribution using 2% w/w f‐MPC 85 and 60% w/w oil. The emulsion remained stable for 14 days at room temperature with no sign of syneresis. f‐MPC85 stabilized emulsions showed rapid shear thinning behavior whereas emulsions containing NaCas showed a gradual decrease in viscosity with an increase in the shear rate. f‐MPC85 showed good emulsifying property and emulsion stability compared to c‐MPC85 and NaCas and it can be an excellent alternative to sodium caseinate in food applications. Practical applications: This study highlights the enhanced emulsifying properties of MPC functionalized (f‐MPC) by the supercritical CO2 extrusion process. The f‐MPC showed better emulsion activity index, reduced creaming index, and comparable viscosity as compared to commercial sodium caseinate. The improved properties of f‐MPC make it a promising product that can be commercialized as an alternative to non‐dairy sodium caseinate.